Enhancing Reading Literacy in Transitional Societies: Methodological Interventions in the Albanian K–12 Context - Macaj, Edlira; Mëniku, Linda (European Journal of Social Science Education and Research, 2025)
This study examines reading literacy challenges in Albania’s K–12 education system, with a focus on instructional practices, teacher strategies, and institutional factors that affect comprehension and literary analysis. Using a mixed-methods design, the research combined theoretical analysis with a nationwide questionnaire completed by 143 language and literature teachers. Findings indicate that teachers demonstrate strong awareness of contemporary reading strategies, including critical questioning, debate, comparative analysis, creative rewriting, and dramatization. However, these methods are applied inconsistently due to limited professional training, rigid curricular requirements, and insufficient institutional support. Based on the results, the study proposes integrative, innovation-oriented interventions to strengthen students’ critical, interpretive, and creative reading competencies. These interventions aim to bridge the gap between pedagogical knowledge and classroom implementation, enhance engagement with texts, and contribute to broader educational improvement. The findings offer actionable insights for improving reading literacy in transitional educational contexts and supporting student-centered, evidence-informed teaching practices.
Keywords: reading literacy, instructional methodology, innovative pedagogical strategies, K–12 education, transitional societies, curriculum reform